Public administration Singapore-style - Quah, Jon S. T. (Emerald, 2010)
Singapore was ranked first for the competence of its public officials from 1999 to 2002 by The Global Competitiveness Report. While research has been done on various aspects of public administration in Singapore, there is to date no comprehensive study of the Singapore Civil Service and the statutory boards and their contribution to the attainment of national development goals. The aim of this book is to rectify this gap in the literature by providing a detailed study of public administration Singapore-style. Public administration Singapore-style is characterized by these features: macho-meritocracy; competing with the private sector for talent; low level of corruption; reliance on institutional and attitudinal administrative reforms; reliance on statutory boards to implement socio-economic development programs; effective policy implementation, improving service to the public; and using policy diffusion to solve problems. The books main thesis is that the nature of public administration in Singapore results from the combined influence of Singapores policy context and the various policies introduced by the Peoples Action Party government since it assumed office in June 1959, 50 years ago.
Keywords: Public administration -- Singapore.; elektronické knihy; electronic books